Influencia en los estilos educativos en el aprendizaje de los estudiantes del Centro Educativo Particular San Carlos de la ciudad de Machala. - Sarango Alejandro, Cecilia Beatriz (2013)
The parenting and school educational styles are aspects that desencuentran on student learning, which causes discomfort in the coexistence of the educational community, family and social. This research was part of an analytic, descriptive and explanatory to develop a mental health program that would promote appropriate educational and learning styles developers in students and their families. The methods used were the scientific method, inductive and deductive, analytic-synthetic, descriptive statistics in order to relate the family environment with children's learning, the techniques applied were: test and surveys of students, parents and leader of course, applied individually and in groups. The study population consisted of 25 students, 25 representatives and a teacher leader of the sixth grade of primary school who were enrolled in the academic year 2012-2013 the private school "San Carlos" in the city of Machala. The results reveal that the investigated families are functional, predominantly permissive parenting style; while in school learning style prevails active and pragmatic style. The mental health program raises a dynamic structure that extends from the conceptual, program outline, content description, action plan, schedule and budget, intervention at different times during the school year, it raises the evaluation as part program, which will verify the results, the benefit of the educational community to manage future programs. With the results of the practical consequences is to think of new strategies for school education, with a new concept of integrating family and school learning. Keywords: Parenting styles, learning styles, Mental Health, Health Program.